Avoid Link Failure using Multipath Routing Technique - M.Appa Rao, V.Yashwanth (International Journal of Scientific Research and Management (IJSRM), 2014)
We present a noval method to find an alternative path, after a link failure between source node to destination node. In this project we are using “Multipath routing scheme” & Dijkstra’s algorithm which is a promising routing scheme to accommodate these requirements by using multiple pairs of routes between a source and a destination. Multipath routing is the routing technique of using multiple alternative paths through a network, which can yield a variety of benefits such as increased bandwidth, or improved security. We are also using the Dijkstra's algorithm for the calculation of the shortest distance between the nodes for improving the performance of the routing path.